Climatization systems for Brazilian dental teaching clinics: a narrative review in the context of the COVID-19 pandemic - Magalhães Dias, Alexa; Meggiolaro, Emilly Dutra Amaral; Oliveira , Lisa Morais Fernandes; Veloso , Éwerton Machado; Soares , Mônica Pereira Senra (Revista da ABENO, 2022)
COVID-19 outbreack has reaffirmed the need to maintain ventilation of dental environments properly. This study was carried out to encourage a reflective analysis of the risks of air contamination in Brazilian dental clinics. A narrative review of the literature was carried out on the recommendations of heating, ventilation and air conditioning (HVAC) systems in dental environments, considering the risks of air contamination in Brazilian dental teaching clinics. The literature research was conducted in the PubMed and Google Scholar databases and the main studies that evaluated the climatization systems and portable high efficiency particulate air filtration (HEPA) units in dental environments were included. Furthermore, it were analyzed the guidelines of the Centers for Disease Control and Prevention, the Brazilian National Health Surveillance Agency, the Brazilian Ministry of Health and important institutions of the different countries. After the initial research, a review of the guidelines and articles that assess the use of HEPA units to improve air cleanliness. This analysis was done by different groups of researchers. All documents mentioned that the air quality of the dental offices must follow the protocols in current legislation to ensure the safety of the environs. They reaffirmed that the COVID-19 pandemic makes it imperative that dental environments equipped with air conditioning have mechanical air renewal devices. An alternative for Brazilian dental teaching clinics equipped with mini-splits or window air conditioning could be the installation of exhaust fans and portable HEPA filter units to exchange air and reduce aerosols inside the environments.